An Assessment of Soil Physicochemical and Trace Metal Profiles around Welding Fabrication Areas of Abraka, Delta State, Nigeria - Udo, M. W.; Egboduku, W. O.; Agbogidi, Oghenerioborue Mary; Micheal, O.; Obogbayiro, I. O. (Journal of Science Research and Reviews, 2025)
This study assessed the physicochemical and trace metal profiles of soils around from welding fabrication areas in Abraka, Delta state, Nigeria. Soil samples were collected from a welding (contaminated site) and a control site. Standard laboratory methods (APHA) and (AOAC) were used to analysed soil parameters and metal concentrations, with results compared against World Health Organization (WHO) limits. The welding-affected soils exhibited higher electrical conductivity and organic matter but lower bulk density content compared to the control site, suggesting better water retention in less-disturbed soils. Moisture content was notably higher in the control soil, suggesting better retention in undisturbed soils. Soil temperature, pH, and water holding capacity also varied between sites. Chemical analysis revealed lower calcium in the contaminated soil but higher magnesium and nitrogen, while phosphorous was reduced relative to the control, all within WHO acceptable ranges. Trace metal analysis showed extremely high levels of nickel and cadmium in the welding-affected soils, far above WHO limits. Other metals, including zinc, iron, lead, cobalt, manganese, copper, chromium, and arsenic, were also elevated relative to the control, although some remained within acceptable limits. The study concludes that welding activities substantially degrade soil quality and increase metal contamination, recommending periodic monitoring, safer waste management, and community awareness to mitigate impacts.